Using constraints for intrusion detection: the NeMODe system - Salgueiro, Pedro (2013)
In this work we present NeMODe a declarative system for Computer Network Intrusion detection which provides a declarative Domain Specific Language for describing computer network intrusion signatures that could spread across several network packets, which allows to state constraints over network packets, describing relations between several packets, and providing several back-end detection mechanisms which relies on Constraint Programming (CP) methodologies to find those intrusions.